2015
DOI: 10.1007/s13187-015-0801-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Symptom Management Education Receiving Patients of Chemotherapy

Abstract: The study of a planned education in patients receiving chemotherapy can alleviate the side effects of chemotherapy and, thus, can increase the quality of the patients' lives. In accordance with this view, this study was conducted with the purpose of examining the effect of planned education given to patients receiving chemotherapy on their symptom control. The study was quasi-experimental. A sample of 140 patients participated, of which 70 were in the experimental group and 70 were in the control group. A pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Kurtz et al, (2007) concluded that training control of symptoms in cancer patients undergoing chemotherapy for the first time causes improved and mitigated symptoms including pain, fatigue, and insomnia in them. Sahin and Erguney (2016) noted that training management and control of symptoms to cancer patients undergoing chemotherapy results in a significant reduction in symptoms including nausea, vomiting, anxiety, fatigue, and sleep disorders. Mollaoglu and Erdogan (2014) concluded that implementing a well-planned educational model in patients undergoing chemotherapy significantly decreases symptoms including nausea, vomiting, constipation, pain, oral and pharyngeal problems, problems of the skin and nails, anorexia, weight changes, anxiety, fatigue, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Kurtz et al, (2007) concluded that training control of symptoms in cancer patients undergoing chemotherapy for the first time causes improved and mitigated symptoms including pain, fatigue, and insomnia in them. Sahin and Erguney (2016) noted that training management and control of symptoms to cancer patients undergoing chemotherapy results in a significant reduction in symptoms including nausea, vomiting, anxiety, fatigue, and sleep disorders. Mollaoglu and Erdogan (2014) concluded that implementing a well-planned educational model in patients undergoing chemotherapy significantly decreases symptoms including nausea, vomiting, constipation, pain, oral and pharyngeal problems, problems of the skin and nails, anorexia, weight changes, anxiety, fatigue, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo de intervenção demonstrou que a educação sobre os sintomas fornecida a pacientes oncológicos em tratamento quimioterápico diminuiu a frequência, gravidade e grau de desconforto causado pelo tratamento (18) .…”
Section: Métodounclassified
“…Indeed, the patients were unprepared for what they were going to experience after treatment and lacked knowledge about daily nutrition, exercise and comprehensive treatment. The crucial roles of nursing education in symptom control, infection prevention and systematic assessment of side effects for patients receiving chemotherapy were stressed in many studies (Sahin & Erguney, 2016). This unpreparedness could be adversely affecting patient confidence for decision-making and involvement in self-care, resulting in their feelings of uncertainty, psychological distress and loss of control.…”
Section: Introductionmentioning
confidence: 99%
“…This unpreparedness could be adversely affecting patient confidence for decision-making and involvement in self-care, resulting in their feelings of uncertainty, psychological distress and loss of control. The crucial roles of nursing education in symptom control, infection prevention and systematic assessment of side effects for patients receiving chemotherapy were stressed in many studies (Sahin & Erguney, 2016). Booklets, brochures and assistance from professionals were the most common sources of information for patients experiencing the diagnosis and treatment phases (Rutten et al, 2005).…”
Section: Introductionmentioning
confidence: 99%